Students’ Perception about Online Language Exchange Program to Enhancing Their English-Speaking Ability - Desla Fitria; Agus Wijayanto (Universitas Cokroaminoto Palopo, 2024)
This study is about students’ perception online language exchange program to enhancing their English-speaking ability. The current study is descriptive qualitative study. The main aims of this study to discuss students' perceptions of the virtual language exchange program towards improving English speaking skills. This study involved three Muhammadiyah University Surakarta students who had participated in a 6-month virtual student exchange program with PSU University. The technique collecting data is interviews. Interviews were conducted by asking the same eight questions to each respondent. The results indicate that after participating in the virtual exchange program, respondents felt that their English-speaking abilities had improved.